Ritual Wisuda: Liminalitas, Komodifikasi dan Ambivalensi Makna - St. Junaeda (Indonesian Journal of Pedagogical and Social Sciences, 2026)
Abstract. This article examines graduation rituals in the context of modern society by highlighting three key aspects: liminality, commodification, and the ambivalence of meaning. Using a cultural anthropology approach, data were obtained through interviews and observations to understand how graduation is interpreted by social actors. The results show that graduation not only functions as a rite of passage marking the change in status from student to graduate, but also as a liminal space that enables the transformation of social identity. However, in practice, this ritual is commodified through the involvement of various forms of consumption such as photography services, dress rentals, makeup, and celebrations, which expand the meaning of graduation into the realm of social representation. This situation gives rise to an ambivalence of meaning, where graduation is understood simultaneously as an academic achievement and as a performative arena for displaying social status. Thus, graduation rituals reflect the cultural dynamics of modern society, characterized by negotiations of meaning between academic values, consumption practices, and the construction of social identity. Keywords: Gradiation Ritual, Liminality, Commodification, Ambivalence of Meaning